Prediction of Progression to Severe Disease in Women With Late Preterm Hypertensive Disorders of Pregnancy. Issue 4 (December 2017) - Zwertbroek, E.F.; Broekhuijsen, K.; Langenveld, J.; van Baaren, G.J.; van den Berg, P.P.; Bremer, H.A.; Ganzevoort, W.; van Loon, A.J.; Mol, B.W.; van Pampus, M.G.; Perquin, D.A.; Rijnders, R.J.; et al.
Abstract : ( Acta Obstet Gynecol Scand. 2017;96(1):96–105) Hypertensive disorders of pregnancy (HDP) complicate ∼10% of all pregnancies and are strongly associated with maternal morbidity and mortality, as well as with neonatal stillbirth and morbidity. The only effective treatment to prevent maternal or fetal complications in HDP is delivery, but preterm delivery may result in short-term neonatal morbidity (eg, respiratory distress syndrome) or morbidity beyond the neonatal period, such as neurological developmental problems, school-related problems, and impaired growth.